Nickel layer consumption during reflow soldering between Sn-Ag-Cu and ENEPIG [compact disc] - 214468 Jalilah Che Mohamed (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Bahan)) - Universiti Teknologi Malaysia, 2006